2012
DOI: 10.1186/1465-9921-13-38
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of simvastatin on IL-13-induced cytokine gene expression in primary mouse tracheal epithelial cells

Abstract: BackgroundAsthma causes significant morbidity worldwide in adults and children alike, and incurs large healthcare costs. The statin drugs, which treat hyperlipidemia and cardiovascular diseases, have pleiotropic effects beyond lowering cholesterol, including immunomodulatory, anti-inflammatory, and anti-fibrotic properties which may benefit lung health. Using an allergic mouse model of asthma, we previously demonstrated a benefit of statins in reducing peribronchiolar eosinophilic inflammation, airway hyperrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…In terms of biological plausibility, animal studies utilising allergic mouse models showed that statins have anti-inflammatory, anti-remodelling and immunomodulatory effects that attenuate airway hyper-reactivity and improve lung function 6 8 22. Although less work has been performed on mechanisms of action in lung resident cells, there is evidence of significant action in airway smooth muscle cells, fibroblasts, endothelial cells and epithelial cells in vitro 23 24. Given the pleiotropic biological effects, widespread use and reasonable safety record of statins, they may be a potential novel therapy for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of biological plausibility, animal studies utilising allergic mouse models showed that statins have anti-inflammatory, anti-remodelling and immunomodulatory effects that attenuate airway hyper-reactivity and improve lung function 6 8 22. Although less work has been performed on mechanisms of action in lung resident cells, there is evidence of significant action in airway smooth muscle cells, fibroblasts, endothelial cells and epithelial cells in vitro 23 24. Given the pleiotropic biological effects, widespread use and reasonable safety record of statins, they may be a potential novel therapy for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of statins on inflammation and remodelling have been studied mainly using simvastatin in animal models of allergic asthma. Simvastatin has been shown to inhibit epithelial IL-13-inducable pro-inflammatory cytokine production [230]. Ahmad et al [231] showed that simvastatin in a murine model resulted in reduction in inflammatory cell infiltration, mucus hypersecretion, epithelial injury, collagen deposition and AHR.…”
Section: Statins Metformin and Vitamin Dmentioning
confidence: 98%
“…TGF-b can induce pulmonary fibrosis and impair lung function in mice [54]. Taken together these findings and those from other pre-clinical studies [34,55,56] suggest that atorvastatin could potentially attenuate airway remodelling in chronic asthma.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore the enhancing effects of simvastatin on fluticasone effects are thought to be mediated through the up-regulation of indoleamine 2, 3-dioxygenase and IL-10, together with down-regulation of IL-6 and IL-23 expression in myeloid dendritic cells [33]. Atorvastatin has no effect on IL-10 expression on primary mouse tracheal epithelial cells [34]. IL-12p70 was reduced by atorvastatin and sCD40L by both atorvastatin and atorvastatin with ICS: both cytokines have been shown to be reduced by statins [35,36].…”
Section: Discussionmentioning
confidence: 98%